(untitled) (CIPEEX, 2022)
PERSISTENT INFECTION BY THE ONCOGENIC TYPES OF HUMAN PAPILLOMAVIRUS (HPV) IS A CAUSAL FACTOR FOR THE DEVELOPMENT OF CERVICAL CANCER AND ITS PRECURSOR LESIONS, WITH TYPES 16 AND 18 BEING THE MAIN ASSOCIATED WITH CARCINOMA. AMONG THE RISK FACTORS THAT TRIGGER IT ARE EARLY SEX, SMOKING, PREGNANCY, USE OF ORAL CONTRACEPTIVES AS WELL AS THE AGE GROUP IN WHICH THE INDIVIDUAL IS. THE OBJECTIVE WAS TO RELATE THE RISK FACTORS ASSOCIATED WITH HUMAN PAPILLOMAVIRUS AND TO DISCUSS THE DEVELOPMENT OF CARCINOGENIC LESIONS IN THE CERVIX, AS WELL AS TO ANALYZE THE KNOWLEDGE OF THE POPULATION ABOUT THIS TOPIC. THE METHODOLOGY USED WAS THE RESEARCH IN THE SCIELO DATABASE, USING THE FOLLOWING BIREME DESCRIPTORS: PAPILLOMAVIRIDAE, CERVIX, RISK FACTORS AND SMOKING. FIVE ARTICLES WERE SELECTED THAT PRESENTED MORE SCIENTIFIC RIGOR AND DISCUSSED THIS TOPIC. IT WAS OBSERVED THAT, IN THE GROUP AT RISK FOR HPV INFECTION, WOMEN BETWEEN THE AGES OF 19-24, PREGNANT WOMEN, SMOKERS, USERS OF ORAL CONTRACEPTIVES WHO HAD NO KNOWLEDGE OF THIS DISEASE WERE FOUND. IT WAS CONCLUDED THAT HPV IS A MAJOR PROBLEM IN HEALTH CARE AND THAT THE MOST VULNERABLE GROUPS SHOULD BE PRIORITIZED IN PREVENTION ACTIONS. IN ADDITION, CAMPAIGNS SHOULD BE CARRIED OUT TO RAISE AWARENESS OF THE POPULATION ABOUT THE SYMPTOMS, PREVENTION AND FORMS OF TRANSMISSION OF HUMAN PAPILLOMAVIRUS.